Strategi Mudabbir dalam Membentuk Karakter Disiplin Santri di Pondok Pesantren - Irgi Ahmad Fauzi; Ahmad Rosidi (Universitas Muhammadiyah Mataram, 2026)
The formation of students’ disciplinary character is an important aspect of Islamic boarding school education because discipline becomes the foundation for responsibility and obedience to Islamic values. This study aims to analyze the strategies of mudabbir in developing students’ disciplinary character at Pesantren Al Qodiri I Jember. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and validated through data triangulation. The results showed that mudabbir implemented several strategies, including habituation, role modeling, supervision, personal approaches, reward and punishment, and evaluation. These strategies were carried out continuously, not only to encourage students’ compliance with regulations but also to develop awareness, responsibility, and disciplinary habits in their daily lives.